AKUNTABILITAS TRACK ACCESS CHARGE PERKERETAAPIAN INDONESIA - Aurida Mahelvi; Dewi Casmiwati (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2026)
This article analyzes the accountability of the Track Access Charge (TAC) policy in Indonesia’s railway sector. The study employs a qualitative conceptual approach through policy document analysis. The analytical framework is grounded in Bovens’ theory of public accountability, enriched by Romzek and Dubnick’s concepts of bureaucratic and public financial accountability, as well as Behn’s notion of performance accountability. Data are derived from audit reports issued by the Audit Board of the Republic of Indonesia, statutory regulations governing TAC and Non-Tax State Revenue (PNBP), and relevant scholarly literature. The analysis focuses on identifying the relationships among policy actors, accountability mechanisms, and policy outcomes. The findings indicate that although the TAC policy is supported by a robust regulatory framework, its implementation continues to face major challenges, particularly limited transparency in cost calculation, fragmented oversight among actors, and tensions between fiscal objectives and the improvement of railway service performance. This article argues that TAC accountability should be understood as an instrument of public financial governance oriented toward performance and public value, rather than merely as a form of administrative compliance.